The Effects of Covid-19 on Global Tourism - Harchandani, Priya; Shome, Samik (ASEAN Journal on Hospitality and Tourism, 2021)
The world is facing an unprecedented situation with Covid-19 posing many socioeconomic challenges to tackle. While projections of UNWTO suggest that international tourist arrivals could decline by 60-80% for 2020, global tourism has once again come under the radar of crises. The aim of this study is to explore and discuss the ramifications of the pandemic on global tourism and its allied industries. For the same, a regional assessment has been carried out on global tourism and three associated industries including airlines, hospitality with special focus on the hotel segment and the MSMEs involved directly in tourism. Region-wise analysis reveals that Asia-Pacific region has been the most affected followed by Europe and America due to the restrictions imposed on travel and tourism sector across nations. The paper also discusses the policy responses taken by economies across the world and provides an overview of the future policy decisions which will be crucial for the sustenance of the global tourism sector. Tourism, a resilient and flexible sector, requires several structural adjustments in order to survive and recover. Even with countries opening up their borders and encouraging tourism, the sector is gripped by the challenge of rebuilding consumer confidence in order to promote future tourism. Globalization has led to increased susceptibility of tourism to crises and sustainability powered with innovation may be the way out for the sector.